2015
DOI: 10.2147/lctt.s60427
|View full text |Cite
|
Sign up to set email alerts
|

Epiregulin as a therapeutic target in non-small-cell lung cancer

Abstract: Epiregulin (EREG) belongs to the ErbB family of ligands. EREG binds to EGFR and ErbB4 receptor and stimulates homodimers of EGFR and ErbB4 in addition to all possible heterodimeric ErbB complexes, resulting in the activation of downstream signaling pathways. EREG is overexpressed in various human cancers and has been implicated in tumor progression and metastasis. Oncogenic activation of the MEK/ERK pathway plays a central role in the regulation of EREG expression. Non-small-cell lung cancers (NSCLCs) harborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Further, PGE 2 has been reported to promote AREG induction and to stimulate growth of colon cancer cells [ 72 ]. Similarly, elevated EREG expression in NSCLC is associated with aggressive tumor phenotypes and unfavourable prognosis [ 73 75 ]. Additionally, in several tumor cell lines, COX-2 and EREG have been identified as metastasis associated genes [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, PGE 2 has been reported to promote AREG induction and to stimulate growth of colon cancer cells [ 72 ]. Similarly, elevated EREG expression in NSCLC is associated with aggressive tumor phenotypes and unfavourable prognosis [ 73 75 ]. Additionally, in several tumor cell lines, COX-2 and EREG have been identified as metastasis associated genes [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no ligand for HER2; however, EGFR can be activated by several ligands (Table 2) [32], [33]. The function of individual receptors depends on the biological role of corresponding ligands, which have been shown briefly in the Table 2 [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50]. Nevertheless, ligand-induced EGFR may initiate cellular signaling by promoting a homodimer formation with another receptor molecule (homodimerization) or through transactivation with other family members (heterodimerization) including HER2 [32].…”
Section: The Egfr and Its Familymentioning
confidence: 99%
“…EREG functions by specific binding to its receptor EGFR (ErbB), which causes the activation of tyrosine kinases and ultimately regulates cell activity [32]. Studies have shown that the expression of EREG was associated with various tumor diseases such as lung cancer, gastric cancer and colon cancer, which revealed that EREG played an important role in the occurrence and development of tumors [33][34][35]. Recent studies revealed that porcine EREG played an important role in oocyte development and maturation, and the expression of EREG enhanced the repair of wounds [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%